Gambaran Penggunaan Antidepresan Pada Pasien Lanjut Usia - Danang Sigit Widianto; Nurmainah Nurmainah; Mohamad Andrie (Journal Syifa Sciences and Clinical Research, 2023)
Depression is a common mental disorder characterized by a loss of interest or pleasure. The types of drugs used in the use of antidepressants include selective serotonin reuptake inhibitors (SSRIs), selective serotonin-norepinephrine reuptake inhibitors (SNRIs), and tricyclics. The purpose of this study was to describe the patient's description, the level of depression, and the types of antidepressant drugs used in elderly patients hospitalized at Sei Bangkong Hospital, Pontianak. Methods This research is a descriptive observational study with a cross sectional design. Data collection was carried out by using medical record data during the 2021 period using antidepressants. The results showed that the age of patients 61-65 years old who used antidepressants were 20 people (51.28%), while for 65 years who used antidepressants were 19 people (48.71%). The level of minor depression was 20 people (51.28%), while for major depression it was 19 people (48.71%). The types of drug classes used are SSRI group, SNRI group, and tricyclic group. The conclusion of this study is that there are more patients aged 61-65 years than patients 65 years who are depressed, female and male with minor and major depression levels. The types of drug classes used are SSRI group, SNRI group, and tricyclic group.